2021
DOI: 10.1021/acsami.1c13249
|View full text |Cite|
|
Sign up to set email alerts
|

Photo-Driven Delivery of 125I-Labeled Nanomicelles for Nucleus-Targeted Internal Conversion Electron-Based Cancer Therapy

Abstract: As a kind of high linear energy transfer (LET) radiation, internal conversion electrons are emitted from some radionuclides, such as 125I, triggering severe DNA damage to tumor cells when transported into the nucleus. Herein, we develop a curcumin-loaded nanomicelle composed of a photosensitizer chlorin e6 (Ce6) and amphiphilic poly­(ethylene glycol) (poly­(maleic anhydride-alt-1-octadecene)-poly­(ethylene glycol) (C18-PMH-PEG)) to deliver 125I into the nucleus under 660 nm laser irradiation, leading to the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…4T1 cells showed increased TUNEL positive signals after 4 Gy X-ray irradiation with AZ, indicating the enhanced DNA damage (Figure d) . γ-H2AX is a marker used to confirm DNA DSBs. , Figure e displays that 4T1 cells treated with AZ also showed higher γ-H2AX expression, which means that AZ induces DNA DSBs in 4T1 cells following RT.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…4T1 cells showed increased TUNEL positive signals after 4 Gy X-ray irradiation with AZ, indicating the enhanced DNA damage (Figure d) . γ-H2AX is a marker used to confirm DNA DSBs. , Figure e displays that 4T1 cells treated with AZ also showed higher γ-H2AX expression, which means that AZ induces DNA DSBs in 4T1 cells following RT.…”
Section: Resultsmentioning
confidence: 88%
“…47 γ-H2AX is a marker used to confirm DNA DSBs. 48,49 Figure 3e displays that 4T1 cells treated with AZ also showed higher γ-H2AX expression, which means that AZ induces DNA DSBs in 4T1 cells following RT.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“… 36 Similarly, Qin et al reported a nucleus-targeted internal conversion electron-based cancer therapy strategy induced by nanomicelles, which was labeled by radionuclide 125 I after the PEG modification on its surface. 37 Thus, it is evident that the radionuclide 125 I labeling method for NCs employing corresponding ligand design cannot be replicated and applied on a large scale. Therefore, it is necessary to establish a more universal radiolabeling method for NCs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Qin group [92] developed Ce6-C 18 -PEG/ 125 I-Cur nano-micelles, amphiphilic poly (maleic anhydride-alt-1-octadecene)-poly (ethylene glycol) (C 18 -PMH-PEG) was grafted with the photosensitizer chlorin e6 (Ce6) to form nano-micelles (Ce6-C 18 -PEG). Then Ce6-C 18 -PEG was combined with the nucleus targeting substance curcumin (Cur), self-assembling to obtain Ce6-C 18 -PEG/Cur nanoparticles, which showed the ability to block the cellular mass exchange and promoting program cell death [93] .…”
Section: Organelle-targeted Rtmentioning
confidence: 99%